Odpowiedzi

Najlepsza Odpowiedź!
2010-01-21T14:47:35+01:00
I) -1+4(2z-1)=3
-1+8z-4=3
-5+8z=3
8z=3+5
8z=8 /:8
z=1
j) 2y+3(4-y)=y
2y+12-3y=y
-y+12=y
12=y+y
2y=12 /:2
y=6
k) 6(3y+2)-5(4y+6)=-6
18y+12-20y-30=6
-2y-18=6
-2y=6+18
-2y=24 /:(-2)
y=-12
l) -7(2z-3)-5(4-3z)=1
-14z+21-20+15z=1
z+1=1
z=1-1
z=0
m) 3=-3(5y+2)-6(3y-7)
3=-15y-6-18y+42
3=-33y+36
3-36=-33y
-33=-33y /:(-33)
y=1
n) 2(7x-3)=5-4(6-4x)
14x-6=5-24+16x
14x-16x=5-24+6
-2x=-13 /:(-2)
x=6,5
p) -3-5(3x-2)=-8
-3-15x+10=-8
-15x=-8+3-10
-15x= -15 /:(-15)
x=1
q) 4z-3(3z-5)=2z+1
4z-9z+15=2z+1
-5z-2z=1-15
-7z=-14 /:(-7)
z=2
1 5 1
2010-01-21T14:53:10+01:00
I) 1+4(2z-1)=3
-1+8z-4=3
-1-4-3=-8z
-8=-8z
-8z=-8/(-8)
z=1

j) 2y+3(4-y)=y
2y+12-3y=y
2y-3y-y=-12
-2y=-12/(-2)
y=6

k) 6(3y+2)-5(4y+6)=-6
18y+12-20y-30=-6
-2y=-6-12+30
-2y=-12/(-2)
y=6

l) -7(2z-3)-5(4-3z)=1
-14z+21-20+15z=1
z=1-12+20
z=0

m) 3=-3(5y+2)-6(3y-7)
3=-15y-6-18y+42
15y+18y=-6+42-3
33y=33/33
y=1

n) 2(7x-3)=5-4(6-4x)
14x-6=5-24+16x
14x-16x=5-24+6
-2x=-12/(-2)
x=6calych 1/2

p) -3-5(3x-2)=-8
-3-15x+10=-8
-15x=-8+3-10
-15x=-15/(-15)
x=1

q) 4z-3(3z-5)=2z+1
4z-9z+15=2z+1
-5z-2z=1-15
-7z=-14/(-7)
z=2




w k) ma byc y=6 tamten człowiek źle zrobił
1 5 1